2022
DOI: 10.1097/qad.0000000000003469
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response durability following three-dose coronavirus disease 2019 vaccination in people with HIV receiving suppressive antiretroviral therapy

Abstract: Background:Limited data exist regarding longer term antibody responses following three-dose coronavirus disease 2019 (COVID-19) vaccination, and the impact of a first SARS-CoV-2 infection during this time, in people with HIV (PWH) receiving suppressive antiretroviral therapy (ART). We quantified wild-type-specific, Omicron BA.1-specific and Omicron BA.5-specific responses up to 6 months post-third dose in 64 PWH and 117 controls who remained COVID-19-naive or experienced their first SARS-CoV-2 infection during… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 36 publications
12
19
0
Order By: Relevance
“…NtAb titers to BA.5 were significantly lower with respect to titers to B.1 six months after the third dose of the BNT162b2 vaccine in a cohort of HIV-positive subjects, mostly on successful ART. This result is in agreement with previously reported data in patients receiving three vaccine doses and having NtAb tested about one month [5,27] and eight months [28] after the third dose. The subjects enrolled in the first study [27] were HIV-positive patients on ART with a median CD4+ T cell count > 500 cells/mm 3 , while subjects included in the studies by Cheng et al [5] and by Anichini et al [28] were likely HIV-uninfected (no information was reported).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…NtAb titers to BA.5 were significantly lower with respect to titers to B.1 six months after the third dose of the BNT162b2 vaccine in a cohort of HIV-positive subjects, mostly on successful ART. This result is in agreement with previously reported data in patients receiving three vaccine doses and having NtAb tested about one month [5,27] and eight months [28] after the third dose. The subjects enrolled in the first study [27] were HIV-positive patients on ART with a median CD4+ T cell count > 500 cells/mm 3 , while subjects included in the studies by Cheng et al [5] and by Anichini et al [28] were likely HIV-uninfected (no information was reported).…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with previously reported data in patients receiving three vaccine doses and having NtAb tested about one month [5,27] and eight months [28] after the third dose. The subjects enrolled in the first study [27] were HIV-positive patients on ART with a median CD4+ T cell count > 500 cells/mm 3 , while subjects included in the studies by Cheng et al [5] and by Anichini et al [28] were likely HIV-uninfected (no information was reported). Taken together, all these results suggest that the striking divergence of Omicron BA.5 is the major driver for vaccine escape and that the NtAb response in immune restored HIV-positive subjects is similar to that occurring in HIV-negative patients [27,29].…”
Section: Discussionsupporting
confidence: 93%
“…At 6 months after the third vaccination, the efficacy of the NAb response against the SARS-CoV-2 strains was inadequate in both cohorts; this was especially true for the Omicron BA.5.2 variant. A similar phenomenon was reported by Lapointe et al and Zhan et al (10,13). Given that none of the PLWH exhibited neutralization activity against Omicron BA.5.2, we analyzed the sera from HCs to see whether the persistent immune dysregulation and chronic inflammatory status of PLWH (32) reduced their ability to mount a protective NAb response against Omicron (30).…”
Section: Discussionsupporting
confidence: 64%
“…The weak neutralizing ability of NAbs against Omicron BA.5.2 observed in our study could be attributed to a longer interval for blood collection or the difference between COVID-19 vaccines. Another possible explanation is the differences in the immunogenicity of the BA.5.2 and BA.1 Omicron variants (10,13). At 6 months after the third vaccination, the efficacy of the NAb response against the SARS-CoV-2 strains was inadequate in both cohorts; this was especially true for the Omicron BA.5.2 variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation